Common footprints of the greenhouse gases and air pollutants in China. (15th April 2021) - Liu, Li-Jing; Liu, Lan-Cui; Liang, Qiao-Mei
Abstract: The environmental emissions embodied in supply chains have received increasing attention, but relatively little attention has been paid to common contributors to both greenhouse gas (GHG) and air pollutant emissions. Taking China as an example and applying the environmentally extended multiregional input–output (MRIO) model and the structural path analysis method, this study investigated both the GHG and air pollutant emissions embodied in the common supply chains in 2012. The results show that co-control of both GHGs and pollutants fell into two categories: carbon dioxide (CO2 )and pollutants (sulfur dioxide (SO2 ), nitrogen oxide (NOx), fine particulate matter (PM2.5 ), black carbon (BC), organic carbon (OC), and carbon monoxide (CO)), and non-CO2 (methane (CH4 ) and nitrous oxide (N2 O)) and pollutants (BC, OC, and ammonia (NH3 )). The key paths for the former category include "Nonmetal products → Construction → Fixed Capital Formation" in 18 provinces and "Electricity and heat → Urban Household Consumption" in 7 provinces. The key paths for the latter category include agricultural production driven by different final demands, especially urban household consumption.